Uji Kualitas Air Keran Pada Laboratorium Terpadu Universitas UIN Raden Fatah Palembang - ., Pira blen siska; ., violita argentina; ., muhammad bayumi (CV. ITTC INDONESIA, 2023)
Water Quality is a term that describes the suitability or suitability of water for certain uses, for example: drinking water, fisheries, irrigation, industry, recreation and so on. Caring about water quality means knowing the condition of the water to ensure safety and sustainability in its use. Water quality can be determined by carrying out certain tests on the water. Tests that are usually carried out are chemical, physical, biological tests, or appearance tests (smell and color). For more complex measurements, water samples are needed which are then maintained, transferred and analyzed elsewhere (for example, a laboratory). Measurements like this have two problems, namely that the characteristics of the water in the sample may not be the same as the source because chemical and biological changes occur over time. Even water quality can vary between day and night and is influenced by the presence of aquatic organisms.